17 Cancer screening may cause overdiagnosis in japan. (4th December 2019) - Takahashi, Hirokazu; Matsumoto, Akiko; Nakayama, Tomio
Abstract : Objectives: Since cancer screening started as a national program in 1983 in Japan, there has been a divergence between morbidity and mortality rates in several cancers, and overdiagnosis has progressed. Methods: Overdiagnosis was inferred from the annual change in morbidity and mortality rates of each cancer and the rate of cancer screening conducted by the local government. Results: In 27 years from 1985, there was a divergence between morbidity and mortality in breast, prostate, lung and uterine body cancer. In breast cancer, cancer in the epithelium increased. In prostate cancer, morbidity has increased sharply since 2003. In lung cancer, there was a divergence between morbidity and mortality, but mortality tended to decrease. Conclusions: From the viewpoint of cancer prevention, cancer screening is one of the effective policies. It is necessary to have a system to properly carry out effective cancer screening that can reduce mortality in the long term.